Designing an Android-Based Mobile Learning Media for Teaching English Future Tenses - Nugraha, Bayu Dwiyanto; Regina, Regina; Rezeki, Yanti Sri (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2024)
The purpose of this research was to design android-based media for teaching, simple future tense, future continuous tense, future perfect tense, future perfect continuous tense. In this research, the method was development research that used ADDE instructional design as the procedures in developing the media. The android-based mobile learning media is intended to be supplementary android-based mobile learning media in teaching future tenses. The android-based mobile learning media was assessed by the experts according to several aspects, including the user interface, user experience, and the effectiveness of the android-based mobile learning media for teaching in the classroom. The total score of the expert assessment of the media and design was 93.05 by the maximum score was 100% and total score of the expert assessment of the content criteria was 95.83% by the maximum score was 100%. The experts’ assessment result showed that the media was suitable and in good quality to be used by the teacher and students as media for teaching future tenses.